Edukasi Pentingnya Menjaga Kebugaran Jasmani Melalui Senam Petani Bagi Masyarakat Desa Waringinkarya - Gani, Ruslan; Subandi, Oman Unju; Sutirna, Sutirna; Gustiawati, Resty; Achmad, Irfan Zinat (Jurnal Sosial & Abdimas, 2025)
The people of Waringinkarya village still do not understand how to properly implement physical fitness, and they also engage in irregular and unstructured physical activities, resulting in many mistakes in applying habits in fitness activities. This community service programme provides understanding and guidance on how to properly and correctly implement physical fitness activities. The purpose of this community service is to provide knowledge and insight related to understanding how to carry out proper and correct physical fitness activities. The participants of this activity are residents of Waringinkarya village, with a total of 30 participants. The methods used in this activity include interviews, socialisation, and training. Data collection was carried out by distributing activity questionnaires. This activity increased the knowledge of the women's exercise group about physical fitness in performing physical fitness activities. This community service activity ran well and there was an increase in participants' understanding of how to perform good and proper physical fitness activities, as experienced by the participants, namely before participating in the activity with a pre-test score of 10.9 and after participating in the activity with a post-test score of 17.3. There was a 32% increase in understanding of physical fitness activities. The implementation of this community service activity has helped to raise awareness of the importance of maintaining health and fitness and has encouraged the community to engage in physical fitness activities.   Masyarakat Desa Waringinkarya masih belum memahami tentang pelaksanaan kebugaran jasmani dengan baik, dan juga masyarakatnya dalam melakukan aktivitas gerak tidak teratur dan terstruktur sehingga masih banyak yang salah dalam menerapkan pola pembiasaan dalam aktivitas kebugaran. Program pengabdian ini memberikan pemahaman dan bagaimana pelaksanaan melakukan aktivitas kebugaran jasmani yang baik dan benar. Tujuan dari pengabdian ini memberikan pengetahuan dan wawasan terkait pemahaman dalam melaksanakan aktivitas kebugaran jasmani yang baik dan benar. Peserta kegiatan merupakan masyarakat desa Waringinkarya dengan jumlah peserta 30 orang. Metode yang digunakan dalam kegiatan ini meliputi wawancara, sosialisasi, dan pelatihan. Pengambilan data dilakukan dengan menyebarkan angket/kuesioner kegiatan. Kegiatan ini menambah pengetahuan kelompok ibu-ibu senam tentang kebugaan jasmani dalam melakukan aktivitas kebugaran jasmani. Kegiatan pengabdian kepada masyarakat ini berjalan dengan baik dan terdapat peningkatan pemahaman peserta mengenai bagaimana melakukan aktivitas kebugaran yang baik dan benar yang dialami peserta yaitu sebelum mengikuti kegiatan dengan hasil pre test 10,9 dan setelah mengikuti kegiatan setelah post test 17.3. Terjadinya peningkatan pemahaman aktivitas kebugaran jasmani sebesar 32%. Dengan dilaksanakannya kegiatan pengabdian ini dapat menumbuhkan kesadaran diri pentingnya menjaga kesehatan dan kebugaran dan adanya kesungguhan pada masyarakat untuk melaksanakan aktivitas kebugaran jasmani.